High Ki-67 and Vascular Endothelial Growth Factor (VEGF) Protein Expression as Negative Predictive Factor for Combined Neoadjuvant Chemotherapy in Young Age Stage III Breast Cancer - Sudarsa, I. W.; Manuaba, I. B. Tjakra W.; Maliawan, Sri; Sutirtayasa, I. W. P. (BALI MEDICAL JOURNAL, 2016)
Background: Breast cancer was, in general, a heterogeneous disease with diverse biological characteristics, types, subtypes and clinical behavior. Its treatment and management need to be personalized and individualized. Breast cancer in young ages, although rare, is usually a unique and more aggressive cancer associated with poorer prognosis. The combination of young age and advanced stages of breast cancer would make this particular breast cancer harder to treat and cure. Unfortunately, majority of Breast Cancer Patients in Bali were in younger ages, and at advanced stages, that the mainstay of treatment was neo adjuvant chemotherapy followed by other treatment modalities. Improve prognosis only, those patients who had had a complete pathological response involving primary tumor and regional lymph nodes in the axilla. Several factors had been studied and contributed to breast cancer response to combined neo-adjuvant chemotherapy. Usually, younger patients, was associated with high proliferation rate represented by Ki-67 and early distant metastasis represented by VEGF, which also had role as prognostic markers. The purpose of this study was to determine whether high Ki-67 and VEGF expression correlate with response to NAC and hence, they would be important predictive factors for response to NAC. Method: This study was a cross-sectional and a nested case-control study of stage III breast cancers affecting patients 40 years of age or less, at Sanglah General Hospital and Prima Medika Hospital, conducted from September 1st, 2012 until March 31st, 2014. Clinical and pathology reports were traced and recorded from both hospitals; routine Immunohistochemistry (IHC) examinations were performed by both pathology labs. Statistical analysis was performed using Chi-Square test, Odds Ratio (OR), and logistic regression analysis with p<0.05. Results: There were 66 Stage III young breast cancer patients, where 35 (53%) showed no or negative response and 31 (47%) showed a positive response. Cross-sectional analysis showed that there was a significant correlation between positive Ki-67 protein expression and response to NAC (p<0.05; OR 5.538; 1.856 – 16.524; 95% C.I.) and between positive VEGF protein expression and response to NAC (p<0.05; OR. 3.455; 1.251-9.539; 95% C.I.). In Case-Control study, bivariate analysis from 62 samples had shown that higher Ki-67 expression in the study group compared to control group (p=0.004; OR. 4.747; 1.575-14.312; 95% C.I.). Bivariate analysis also showed that VEGF expression was also higher in the study group compared to control group (p=0.042; OR.2.879; 1.026-8.074; 95% CI.). Multivariate analysis had shown that an adjusted OR. 4.747 (1.575-14.312; 95% C.I.; p=0.006) for Ki-67, and an adjusted OR. 2.553 (0.860-7.582; 95% C.I.; p=0.091) for VEGF. Conclusion: We concluded that high Ki-67 and VEGF protein expression was associated with less response to combined neo-adjuvant chemotherapy/NAC and that high Ki-67 protein expression was an independent risk factor for poorer response to NAC in Stage III young age breast cancer. The possible role of high VEGF expression as a risk factor for less responsive breast cancer in younger patients had to be considered.
Keywords: Ki-67 protein expression, VEGF expression, poor chemotherapy response, young stage III breast cancer.